Periprocedural safety and efficacy after left atrial appendage closure in a large UK tertiary centre: 10-year experience. (24th May 2021) - Briosa E Gala, A; Pope, MTB; Monteiro, C; Leo, M; Betts, TR
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Left atrial appendage (LAA) thrombus is responsible for up 90% of atrial fibrillation (AF) related ischaemic strokes. Mechanical closure of the LAA is an alternative stroke prevention strategy in patients with non-valvular AF who are at a high risk of bleeding. LAA morphology is highly variable which may affect acute procedural success rates. Purpose: This study sought to examine the periprocedural safety and efficacy, and short-term outcomes in patients undergoing left atrial appendage occlusion (LAAO) device implantation in a large UK tertiary centre. Methods: This retrospective study included all patients listed for a LAAO device in our institution from January 2010 to December 2020. Medical notes, procedural and imaging reports were reviewed and adverse event rates were calculated at discharge, 30 and 90 days. A Cox regression model was used for multivariable analysis with pre-specified covariates to assess outcomes at 90 days. Results: Of 237 patients listed for a LAAO device, 8 (3.4%) had a LAA thrombus and the procedure was abandoned (4 had a successful implant at a later date). In 225 (94.9%) patients a LAAO device was implanted and 4 (1.7%) had unsuitable anatomy precluding device deployment. Seventy-two percent were male, age 74 ± 8 years, BMI 27 ± 6 kg/m2, CHA2DS2-VASc score 4.4 ± 1.2, HASBLED score 3.2 ± 0.8 and at high risk of stroke (98 ischaemic strokes and 129 haemorrhagic strokes) and bleeding (151 major or life-threatening bleeding episodes).  The mean procedural and fluoroscopy time were 52.5 ± 30.5 and 8.0 ± 5.9 minutes, respectively. Three different LAAO devices were used (136 Watchman, 54 Watchman FLX and 35 Amplatzer Cardiac Plug) with no significant difference in acute procedural success (97.8%, 98.2% and 94.4%, p = 0.41, respectively). Complete seal was achieved in 202 (92%) patients with only 1 (0.4%) moderate leak. Procedure-related mortality was 1.3% and non-fatal serious adverse events occurred in 5 (2.1%) patients. At 90 days, 28 patients experienced an adverse event (KM 12.5%; 95% CI, 8%-16.1%) and 16 patients suffered a serious adverse event (KM 7.1%; 95% CI, 3.7%-10.4%). In a covariate-adjusted Cox model, CHA2DS2-VASc score less than 4 had hazard ratio of 0.21 (95% CI, 0.06 -0.71, p = 0.01) for serious events at 90 days. Conclusion: The acute procedural success rate was high (97%) with a low number of periprocedural complications. Serious adverse events at both 30 and 90-days were low in keeping with other published registries.